PRESUPPOSITION FOUND IN THE BBC NEWS: CORONA VIRUS IN INDONESIA - Balqis Majesty Wahana; Ambalegin Ambalegin; Nurma Dhona Handayani (eScience Humanity Journal, 2021)
The aim of the study was to identify and analyze the types of presupposition implied in the BBC news of corona virus in Indonesia. In this research, the researchers used descriptive qualitative research as the research design. The research design was conducted to design is a qualitative approach in which express the outcome in words and provide an explanation of the result. In collecting the data, the researchers used the observational method and non-participatory technique by Sudaryanto (1993). In analyzing data, the researchers applied pragmatic identity method and distributional method. As for the theory, the researchers used the presupposition theory proposed by Yule (1996). The types are existential, factive, non- factive, lexical, structural and the counter factual presupposition. The research was existing in the  BBC news “Indonesia corona virus”. The research found the types of presupposition are existential, factive, non- factive, lexical, structural and the counter factual presupposition. The most type of presupposition which could be found is existential presupposition.